Applying the theory of planned behavior and media dependency theory: Predictors of public pro-environmental behavioral intentions in Singapore - HO, Shirley S. (Institutional Knowledge at Singapore Management University, 2015)
Applying the theory of planned behavior and media dependency theory, this study examines the effects of attitude, subjective norms, perceived behavioral control (PBC), media dependency, traditional media attention, Internet attention, and interpersonal communication on two types of pro-environmental behaviors (PEBs)—green-buying and environmental civic engagement. Regression analysis of a nationally representative survey of adult Singaporeans (N = 1168) indicated that attitude, PBC, media dependency, traditional media attention, and interpersonal communication were positively associated with green-buying. Notably, traditional media attention, as well as interpersonal communication, moderated the influence of media dependency on green-buying behavior. In addition, attitude, descriptive norms, media dependency, Internet attention, and interpersonal communication positively predicted environmental civic engagement. Findings suggest the importance of communication factors in the adoption of the two PEBs.